Time-of-day-dependent effects of exercise on the hepatic clock and proteome in high-fat diet-fed mice - Chunxiu Huang; Xiaodan Wang; Huanghao Zhou; JingFang Zhu; Yue Hu; Huijuan Wu; Xinru Yu; Cong Chen (Journal of Physiology and Biochemistry, 2026)

Radio frequency pasteurization of spices under stationary, moving, and mixing conditions: Linking temperature distribution with microbial inactivation, and moisture uniformity - Yingwen Tang; Shangjiayi Bai; Jincheng Ma; Jingfang Ao; Shaojin Wang; Long Chen (Food Control, 2026)

Mechanisms underlying the impacts of antibiotics on soil microbes and enzyme activities in urban green spaces - Jingfang Li; Liang Chen; Zhibin Jia; Fawen Li (Applied Soil Ecology, 2026)

N-doped hollow carbon nanocage-CNT confined FeNi nanoreactors for PMS activation toward sulfadiazine degradation - Junchang Wang; Yulai He; Jingfang Hu; Limin Chen; Ye Hong; Wenjin Chen (Journal of Water Process Engineering, 2026)

Maturity-driven changes in radio frequency-vacuum drying of kiwifruit: Mechanistic insights from dielectric properties and microstructure evolution - Jingfang Ao; Haihui Zhu; Tingting Xu; Shaojin Wang; Chung Lim Law; Long Chen (Food Research International, 2026)

In situ real-time continuous monitoring of soil carbonate ions using a portable CuO–Cu2O-based electrochemical sensor - Yuying Bao; Jingfang Ji; Jiyu Chen; Kaiquan Li; Pan Liu; Jingmin Ge; Ronghan Wei; Xiaodong Lei; Jingwei Zhang (Analytica Chimica Acta, 2026)

Long-term capsaicin intake and gut inflammation: microbial alterations, metabolic mechanisms, and intervention effects - Liangliang Zhu; Yijia Chen; Jiayang Jin; Mengyao Zhao; Jingfang Ran; Hao Yin; Xiaoguo Ji; Liming Zhao (Food Research International, 2026)

Holistic evolution of the Bohai Sea complex system: Insights from interacting drivers - Han Huang; Tao Zou; Teng Liu; Hongyu Wang; Zhixuan Wang; Ningning Tao; Yanfang Li; Hao Fan; Fei Xie; Weidong Zhai; Guizhi Wang; Yongwen Zhang; et al. (Marine Environmental Research, 2026)

Halovenus anhuiensis sp. nov. and Natronomonas salinimetallica sp. nov., two extremely halophilic archaeon isolated from a salt mine - Ya-Ling Mao; Aodi Zhang; Tao Hong; Yue Ding; Jingfang Liu; Jing Hou; Heng-Lin Cui; Shaoxing Chen (Extremophiles, 2026)

Managing solid waste to co-control carbon and nitrogen leakage in China - Xin Xu; Jingfang Zhan; Tianrun Chen; Xiuming Zhang; Yiyang Zou; Baojing Gu (Resources, Conservation and Recycling, 2026)

Cross-scale long-term spatiotemporal dynamics and influencing indicators of summer urban heat risk in mega-urban agglomeration - Jiachen Liu; Xiaofang Wang; Jingfang Yan; Xinfei Zhao; Wenke Chen; Le Yin; Baolei Zhang (Journal of Cleaner Production, 2025)

An integrated mechanistic modeling and machine learning for radio frequency heating uniformity optimization of canola seeds - Jilong Gao; Yu Liu; Jingfang Ao; Shaojin Wang; Jiajia Chen; Long Chen (Innovative Food Science & Emerging Technologies, 2025)

Multidimensional quality assessment (nutrients and aroma) of dried kiwifruit: Unveiling the advantages of radio frequency-vacuum drying - Jingfang Ao; Shaojin Wang; Xingshu Li; Chung Lim Law; Long Chen (Food Chemistry, 2025)

Effects of woody plant roots on migration of ciprofloxacin and tylosin in soil - Jingfang Li; Huiting Ma; H.U. Xiaoming; Liang Chen; Paul H. Fallgren (Journal of Contaminant Hydrology, 2025)

Investigating spatiotemporal variability of drought and its impact on grassland GPP in Inner Mongolia - Jingfang Zhang; Fanhao Meng; Min Luo; Yixin Fang; Hongguang Chen; Chula Sa; Wenfeng Chi; Yuhai Bao (Journal of Arid Environments, 2025)

The amino acid Ser223 acts as a key site for the binding of Thrips palmi α1 nicotinic acetylcholine receptor to neonicotinoid insecticides - Kun Zhang; Jianwen Chen; Huixiu Huang; Huiqi Wen; Jingfang Yang; Junjie Geng; Shaoying Wu (Pesticide Biochemistry and Physiology, 2025)

Carbon-confinement modulated interfacial water structure for accelerated dissociation kinetics towards hydrogen evolution - Fanpeng Cheng; Yue Yu; Yulu Wan; Dashuai Wang; Shangqing Chen; Jingfang Zhang; Huijuan Guo; Yang Xia; Yi Huang; Lijuan Shi; Liwei Cheng; Qun Yi (Chemical Engineering Journal, 2025)

Prevalence of Avian Influenza Viruses and Biomolecular Analysis of H9N2 Subtype in Live Poultry Markets from 2021 to 2023 in Changsha, China - Xian Zhang; Yutong Wang; Xiaoyu Li; Zheng Huang; Huiyuan Fu; Ruiqing Pei; Caiying Zhu; Yu Di; Shan Chen; Jingfang Chen; Mingzhong Xu; Xuewen Yang; et al. (Food and Environmental Virology, 2025)

Mitofusin 2 Mediates the Protective Effect of NR6A1 Silencing Against Neuronal Injury in Experimental Stroke Models - Bingtian Xu; Zhuhe Liu; Kechun Chen; Qian Zhao; Haixia Wen; Jingfang Lin; Jiangping Xu; Haitao Wang; Honghao Wang; Yuanyuan Wang (Molecular Neurobiology, 2025)

Adding non-crop plants enhances parasitoid fitness on potato plants, but not pest densities - Yusha Wang; Yongping Zhou; Ruwen Li; Ambreen Masqsood; Hongsong Chen; Zhenqiang Qin; Jingfang Yang; Jiali Zhang; Lin Jing; Huihua Tan; Zhongshi Zhou (Crop Protection, 2025)

Oxymatrine reduces hepatic lipid synthesis in rat model of nonalcoholic steatohepatitis by regulating Sirt1/AMPK and LXR/Plin2/SREBP-1c pathways - Jingfang Xiong; Gaofeng Chen; Ying He; Changqing Zhao; Dongya Chen; Yihui Liu; Zhaolin Zhang; Yijun Wu; Hong Xu (Chemico-Biological Interactions, 2025)

Complexity science meets Earth system - Jingfang Fan; Jun Meng; Xiaosong Chen; Hans Joachim Schellnhuber (Science Bulletin, 2025)

Double template synthesis of N/S co-doped shrimp shell derived biochar for efficient sulfadiazine degradation: The role of non-radical pathway - Yulai He; Jiaqi Wang; Lele Lei; Yushi Ai; Hongmei He; Jin Huang; Limin Chen; Jingfang Hu; Wenjin Chen (Journal of Environmental Chemical Engineering, 2024)

Rock-mass heterogeneous rheological properties caused the formation of deep tension fractures - Guoqing Chen; Xiang Sun; Qiang Xu; Sihong Zeng; Jingfang Xing; Xuemin Feng; Fangzhou Liu (Geomechanics for Energy and the Environment, 2024)

SIRT3: A Potential Target of Different Types of Osteoporosis - Binjing Pan; Chongyang Chen; Yangting Zhao; Jing Cai; Songbo Fu; Jingfang Liu (Cell Biochemistry and Biophysics, 2024)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

A pervasive phosphorylation cascade modulation of plant transcription factors in response to abiotic stress - Wang Baoxiang; Sun Zhiguang; Liu Yan; Xu Bo; Li Jingfang; Chi Ming; Xing Yungao; Yang Bo; Li Jian; Liu Jinbo; Chen Tingmu; Fang Zhaowei; et al. (Planta, 2023)

PBX1-promoted SFRP4 transcription inhibits cell proliferation and epithelial-mesenchymal transition in endometrial carcinoma - Liwen Guo; Huihua Chen; Jinguo Chen; Chen Gao; Xianguo Fu; Sujuan Zhou; Wenjuan Wu; Taoping Li; Jingfang Lin; Tailai Yang; Zichun Chen; Luoyuan Cao (Tissue and Cell, 2023)

The neglected potential source of microplastics from daily necessities: A study on protective mobile phone cases - Qilu Li; Meng Yuan; Yuan Chen; Xinjie Jin; Jingfang Shangguan; Jinle Cui; Shixiang Chang; Mengran Guo; Yan Wang (Journal of Hazardous Materials, 2023)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Estimation of Avian Influenza Viruses in Water Environments of Live Poultry Markets in Changsha, China, 2014 to 2018 - Xiaoyu Li; Rusheng Zhang; Zheng Huang; Dong Yao; Lei Luo; Jingfang Chen; Wen Ye; Lingzhi Li; Shan Xiao; Xiaolei Liu; Xinhua Ou; Biancheng Sun; et al. (Food and Environmental Virology, 2022)

Evolution of the novel coronavirus from the ongoing Wuhan outbreak and modeling of its spike protein for risk of human transmission - Xintian Xu; Ping Chen; Jingfang Wang; Jiannan Feng; Hui Zhou; Xuan Li; Wu Zhong; Pei Hao (Science China Life Sciences, 2020)

Hybrids of oxoisoaporphine–tetrahydroisoquinoline: novel multi-target inhibitors of inflammation and amyloid-β aggregation in Alzheimer’s disease - Yusi Chen; Chunlin Su; Li Wang; Jingfang Qin; Shenqi Wei; Huang Tang (Molecular Diversity, 2019)

OsNDUFA9 encoding a mitochondrial complex I subunit is essential for embryo development and starch synthesis in rice - Tingting Hu; Yunlu Tian; Jianping Zhu; Yunlong Wang; Ruonan Jing; Jie Lei; Yinglun Sun; Yanfang Yu; Jingfang Li; Xiaoli Chen; Xiaopin Zhu; Yuanyuan Hao; et al. (Plant Cell Reports, 2018)

Characterization and genomic analyses of Aeromonas hydrophila phages AhSzq-1 and AhSzw-1, isolates representing new species within the T5virus genus - Shengjian Yuan; Ling Chen; Quan Liu; Yan Zhou; Jingfang Yang; Deng Deng; Hongping Li; Yingfei Ma (Archives of Virology, 2018)

Proper balance of omega-3 and omega-6 fatty acid supplements with topical cyclosporine attenuated contact lens-related dry eye syndrome - Ling Wang; Xi Chen; Jingfang Hao; Lu Yang (Inflammopharmacology, 2016)

MicroRNA-135b regulates metastasis suppressor 1 expression and promotes migration and invasion in colorectal cancer - Weiyun Wu; Zhuang Wang; Pengchun Yang; Jingfang Yang; Jian Liang; Yuanhong Chen; Hao Wang; Guoli Wei; Shicai Ye; Yu Zhou (Molecular and Cellular Biochemistry, 2014)

A bFGF Antagonist Peptide with Anti-angiogenesis Properties in Non-small Cell Lung Cancer Cells - Ruixue Wang; Wu Luo; Xiangfeng Zeng; Jingfang Di; Yonglin Yu; Chuan Wang; Wenhui Wang; Xilei Chen; Dan He; Tao Li; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2013)